ASSESSING THE PHYTOCHEMICAL CONTENTS AND ANTIMICROBIAL ACTIVITY OF BITTER LEAF (VERNONIA AMYGDALINA) ON MICRO-ORGANISMS (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Medicinal plants have assumed the basis of traditional medicine and have proven effective in human health care across the world. There is a growing interest in the role of complementary and alternative medicines to treat various illnesses. The continued consumption of antibiotic with little or no impact on bacteria have negatively affected health care delivery. Bitter leaf (Vernonia amygdalina) is a popular shrub belonging to the family Asteraceae and a perennial shrub commonly cultivated as a homestead vegetable and fodder tree in various parts of Nigeria. The current study was conducted to assess the phytochemical constituents and antimicrobial activity of bitter leaf on Candida albicans, Pseudomonas aeruginosa and Staphylococcus aureus. The result of the phytochemical analysis conducted on the root and stem bark of V. amygdalina revealed the presence of alkaloids, tannin, steroids, flavonoids, phenol, and saponins. However, it was found that tannins and phenol were mainly deposited in the plant's stem bark. Also, the antimicrobial analysis conducted revealed that S. aureus was more vulnerable to the ethanol, acetone, and hot aqueous extracts of V. amygdalina. while, P. aeruginosa, and C. Albicans showed sensitivity to ethanol and acetone exposure but failed to react to the hot aqueous extracts. The study concludes that the observed biological reactions shown by the aqueous extracts of V. amygdalina corroborate the traditional application of this plant as an alternative antibiotic.